An Anatomically Preserved Cone-like Flower from the Lower Cretaceous of China - Xin Wang; José B. Diez; Mike Pole; Manuel García-Ávila (Life, 2023)
Although diverse fossil angiosperms (including their reproductive organs) have been reported from the Early Cretaceous, few of them are well-documented due to poor preservation and limited technologies available to apply. For example, paraffin sectioning, a routine technology applied to reveal the anatomical details of extant plants, was hitherto at most rarely applied to fossil plants. This undermines the comparability between the outcomes of studies on fossil and extant plants, and makes our understanding on plants incomplete and biased. Here, we applied paraffin sectioning technology, in addition to light microscopy, SEM, and TEM, to document a fossil reproductive organ, Xilinia gen. nov., from the Early Cretaceous in Inner Mongolia, China. The anatomical details of this new reproductive organ were documented. Xilinia bears a remarkable resemblance to conifer cones, although its ovules are enclosed in carpels. The paradoxical cone-like morphology of Xilinia appears to represent a transitional snapshot of plant evolution that is absent in extant plants.